Model Predictive Control to Maximize the Efficiency in EV Wireless Chargers. - González-González, José Manuel; Triviño-Cabrera, Alicia; Aguado-Sánchez, José Antonio (IEEE, 2021)
The automotive industry is undergoing a transition toward cleaner and more efficient technologies. Electric vehicles (EVs) play a relevant role in this scenario. However, these vehicles continue to suffer from limitations in terms of autonomy and charging times, which can be alleviated with wireless charging technology. This technology facilitates the charging process but has a lower efficiency when compared with conductive chargers. This effect is particularly severe under misalignment conditions and with the usual variations of the battery's electrical features. In order to avoid this disadvantage, this article presents a predictive control algorithm focused on maximizing the charging efficiency. As a novelty, the algorithm sets three configuration parameters in the power converters of the system. The main advantage lies in the fact that it does not need constant monitoring and offers very low response times. This control also improves compatibility with different automobile manufacturers, adding the capacity to work with receivers and batteries with diverse characteristics while complying with international standards. The validity of the proposal is verified by theoretical analysis, simulations, and the experimental results of a 2-kW prototype. The results show the feasibility of the proposed control and the improvement in the efficiency of the system.
https://journals.ieeeauthorcenter.ieee.org/become-an-ieee-journal-author/publishing-ethics/guidelines-and-policies/post-publication-policies/#accepted
Keywords: Vehículos eléctricos; Control de procesos; Estaciones de recarga de vehículos eléctricos; Predictive control; Wireless charging; Electric vehicle